THE THE COMPARISON OF ALTMAN Z-SCORE MODEL, ZMIJEWSKI MODEL, SPRINGATE MODEL,: GROVER MODEL, TO PREDICT BANKRUPTCY MINING COMPANY IN BEI - Jenny Ick, Florentin; Tarigan, Lukas Tarigan (Universitas Kristen Indonesia, 2018)
The times are increasingly growing. This Development be seen in an increase in the technology and business. As we know development in technology like computer, televesion, handphne and others. Development in business is many company establish like bank,insurance, hospital, hotel and other business. By looking at the needs of Man are not limited, make many the loacl investors and foreign investors to establish various kinds company can get a big profit. The Company establish to get big profit. If company have good management will be able to set each company. But sometimess the fact is not in accordance with than in hope. The risk of bankruptcy could happen to all of the company. Generally bankruptcy at risk factor for by the can’t to pay off the debts. The debt is all financial obligastions the company to others who hve not been met where debt is a source of fundes or capital that commes from creditors (Hazmi & Mashariono, 2017) . In the research is used four models in predicting bankruptcy for the companies in research to see the level of accuracy in the possibility of bankruptcy the Altman Z-Score model, Zmijewski model, springate model and grover model.Keywords: Bankruptcy Of Mining Company Can Predict With Altman Z-Score Model, Zmijewski Model, Springate Model And Grover Model.